2024
DOI: 10.3390/biom14030338
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Pigmented Corn (Zea mays L.) and Their Effect on Health

Yaír Adonaí Sánchez-Nuño,
Martín Zermeño-Ruiz,
Olga Deli Vázquez-Paulino
et al.

Abstract: Pigmented corn is a gramineae food of great biological, cultural and nutritional importance for many Latin American countries, with more than 250 breeds on the American continent. It confers a large number of health benefits due to its diverse and abundant bioactive compounds. In this narrative review we decided to organize the information on the nutrients, bioactive compounds and phytochemicals present in pigmented corn, as well as their effects on human health. Phenolic compounds and anthocyanins are some of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 176 publications
0
1
0
Order By: Relevance
“…Studies have shown its antioxidant, anti-inflammatory, and anticarcinogenic capacities, as well as its many effects on metabolic dysregulations like obesity, diabetes, and hypertension. These benefits are attributed to its rich composition, which includes phenolic compounds, anthocyanins, fibers, phytosterols, ferulic acid, phospholipids, fatty acids, et cetera [18,24,30,54].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown its antioxidant, anti-inflammatory, and anticarcinogenic capacities, as well as its many effects on metabolic dysregulations like obesity, diabetes, and hypertension. These benefits are attributed to its rich composition, which includes phenolic compounds, anthocyanins, fibers, phytosterols, ferulic acid, phospholipids, fatty acids, et cetera [18,24,30,54].…”
Section: Discussionmentioning
confidence: 99%